USE OF HORSE IN CREATING ALTERNATIVE TOURISM ACTIVITIES AND PRODUCT RANGE: A NEVŞEHİR CASE - Şenay GÜNGÖR (International Journal of Eurasia Social Sciences, 2016)
Horse farms in Cappadocia that is known as “Katpatuka” (Beautiful Horses’ Country) in Persian language has become an important dynamic in accordance with the meaning of the region in history. The use of horse that has a historical connection with Cappadocia has gradually spread in creating an alternative tourism activity and product range in Nevşehir. A significant increase at horse farms and horse has been recently noticed in the area with spectacular tourism attractions. Horse trekking has been organized in the region in order to see spectacular valleys which cannot be visited by motor vehicles. Gradual increase at interest towards the horse trips organized hourly, daily or weekly in company with professional guides is the indicator of the fact that horsing has reached to a significant point in tourism sector. Moreover, the horse orienteering competition organized in Göreme on 27 March 2015 for the first time in the world has given prominence to the relationship between using horse in tourism and Cappadocia. The purpose of this study was to investigate the use of horse in creating alternative tourism activity and product range that has gradually increased in the region and showed difference rather than the other tourism and sports activities. In order to enlighten the main purpose of the study through an integrative approach, case study as one of the qualitative research methods was chosen as the design of the research. Observation, interview and document analysis as multi-dimensional data collection tools were benefited in the research. It was concluded that the level for using horse in tourism activities of Nevşehir was not at an required level despite the natural and humane riches the region had; if pre-determined tourism policy and tourism investments were supported, significant contributions would be provided for both region and country’s tourism